Developing countries participation in the WTO Dispute Settlement System: how to facilitate? - Donmez, Alara (Department of Commercial Law, 2017)
This dissertation examines the developing countries participation and usage of the World Trade Organization's dispute settlement system. Although the World Trade Organization provides equal rights and obligation to enter into the dispute settlement process for all member countries, the litigation process is complex and costly for developing countries. There are various limitations for developing country participation when they want to use the dispute settlement mechanism and this dissertation mainly discusses the lack of legal and financial means of developing countries. In this regard, this dissertation examines possible solution which could increase developing country participation in the dispute settlement mechanism. These alternative resolutions may address the problem of the participation of developing countries in the dispute settlement system and it also try to develop a more effective working dispute settlement mechanism for developing countries. Therefore, World Trade Organization system could propose significant reforms in the Dispute Settlement Body which encourage developing country participation.